Secretory and circulating bacterial small RNAs: a mini-review of the literature - Yi Fei Wang; Jin Fu (ExRNA)
Abstract Background Over the past decade, small non-coding RNAs (sRNAs) have been characterized as important post-transcriptional regulators in bacteria and other microorganisms. Secretable sRNAs from both pathogenic and non-pathogenic bacteria have been identified, revealing novel insight into interspecies communications. Recent advances in the understanding of the secretory sRNAs, including extracellular vesicle-transported sRNAs and circulating sRNAs, have raised great interest. Methods We performed a literature search of the database PubMed, surveying the present stage of knowledge in the field of secretory and circulating bacterial sRNAs. Conclusion Extracellular bacterial sRNAs play an active role in host-microbe interactions. The findings concerning the secretory and circulating bacterial sRNAs may kindle an eager interest in biomarker discovery for infectious bacterial diseases.